Tinjauan Sosio - Teologis terhadap Konsep Mahar dalam Tradisi Suku Batak Toba - Sugeng Santoso; Uswatun Hasanah; Yohana Natassha (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
Dowry is very important and determining in the traditions of certain social groups. although with different names and methods. The dowry is determined based on an agreement between the man and woman by their respective traditions and customs. However, dowry is often considered a buying and selling transaction as compensation for losses suffered by the woman. This concept of dowry was also implemented by ancient Jewish society in the Old Testament. This shows that dowry has been done since ancient times. Apart from that, the concept of dowry is also carried out by the Batak tribe, known as Sinamot. Therefore, this research aims to explain the concept of dowry in the Old Testament and the concept of sinamot in Toba Batak society. This research uses a qualitative ethnographic method that explains the concepts of dowry and sinamot and the correlation between the two. The data sources used are literature, books, and scientific journals. Giving a dowry cannot be equated with a buying and selling transaction between a prospective husband and a girl's parents. The dowry can be used as a form of appreciation for women and can be used as savings if something happens in the marriage. Likewise, the concept of sinamot is not only used as a dowry but also as a wedding expense. But most importantly, sinamot is used as a bond between clans and as a form of appreciation for the bride. Dowry is very important and determining in the traditions of certain social groups. although with different names and methods. The dowry is determined based on an agreement between the man and woman by their respective traditions and customs. However, dowry is often considered a buying and selling transaction as compensation for losses suffered by the woman. This concept of dowry was also implemented by ancient Jewish society in the Old Testament. This shows that dowry has been done since ancient times. Apart from that, the concept of dowry is also carried out by the Batak tribe, known as Sinamot. Therefore, this research aims to explain the concept of dowry in the Old Testament and the concept of sinamot in Toba Batak society. This research uses a qualitative ethnographic method that explains the concepts of dowry and sinamot and the correlation between the two. The data sources used are literature, books, and scientific journals. Giving a dowry cannot be equated with a buying and selling transaction between a prospective husband and a girl's parents. The dowry can be used as a form of appreciation for women and can be used as savings if something happens in the marriage. Likewise, the concept of sinamot is not only used as a dowry but also as a wedding expense. But most importantly, sinamot is used as a bond between clans and as a form of appreciation for the bride.